QUALITY, OBSOLESCENCE AND UNSUSTAINABLE INNOVATION (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2015)
One of the negative side effects of the consumer society and the increasing number of consumer goods available to the average household is the intransparency of product quality, especially product lifetime. There are many examples on failing products and premature obsolescence. Often this phenomenon is related to companies’ profit maximization strategies (planned obsolescence) and consumer protection policy is mobilized to stop this type of exploitation. The paper applies micro-economic analysis to discuss the problem of optimal product quality (e.g. lifetime) in terms of cost-benefit-analysis and under imperfect information (based on Akerlof’s lemon problem). Given consumers’ actual willingness to pay there is an optimal quality which is lower than the technically possible. If the innovation perspective (Schumpeter’s “creative destruction”) is added to the analysis, increasing global competition and speed of product innovation are identified as core drivers for shorter product lifecycles and tend to be the actual limiting factor of product lifetime (economic vs. technical obsolescence). Even if the goals of sustainable development are included in the analysis, this does not provide an unambiguous argument for long-life products as new products tend to be more eco-efficient. A broader discussion on optimal quality (lifetime) of products is necessary, based on holistic life-cycle assessment of alternative product quality options. And finally: The tendency of increasing aftersales disappointment of consumers’ expectations and conflicts with sustainable development goals need to be addressed in a more general debate on (limits of) consumerism. Minor changes in the laws for protecting consumers (e.g. longer warranty) will not do the job. Keywords: Obsolescence, innovation, quality competition, imperfect information, sustainable development, life-cycle analysis